1989
DOI: 10.1113/jphysiol.1989.sp017536
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of head‐down tilt with low‐dose infusion of atrial natriuretic peptide in man.

Abstract: SUMMARY1. Procedures that increase atrial pressure, such as head-down tilt, result in an increase in plasma atrial natriuretic peptide (ANP) and a natriuresis, but a direct cause-and-effect relationship between these two responses has not been established. This study was undertaken to compare the effects of head-down tilt with exogenous ANP on renal function.2. Eight normal sodium-replete volunteers underwent a 3 h placebo infusion, a 3 h ANP infusion at 1-2 pmol kg-' min-' and a 3 h period of head-down tilt. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…There was no significant difference between overall mean values when comparing the hypoxic and normoxic runs. However, HD stimulated a significant (P < .001) release of ANP in both hypoxic and normoxic conditions, but at 15 and 55 minutes during HD the increase in ANP was 35% less with hypoxia (P < .10).…”
Section: Resultsmentioning
confidence: 89%
“…There was no significant difference between overall mean values when comparing the hypoxic and normoxic runs. However, HD stimulated a significant (P < .001) release of ANP in both hypoxic and normoxic conditions, but at 15 and 55 minutes during HD the increase in ANP was 35% less with hypoxia (P < .10).…”
Section: Resultsmentioning
confidence: 89%
“…Atrial natriuretic peptide (ANP) is a hormone stored in atrial myocytes and released into blood circulation in response to various stimuli the most important being right atrial pressure or stretch, for review, see Ruskoaho (1992). In man, head-out immersion (Ogihara et al 1986, Epstein et al 1987, Leung et al 1987, Warner et al 1991, Nakamitsu et al 1994, or headdown tilt (Allen et al 1989, Arjamaa et al 1992 are among the factors that elevate plasma ANP. Nose et al (1994), measuring the right atrial pressure with an intraluminal catheter, showed a correlation between plasma ANP and right atrial pressure during prolonged exercise in man.…”
mentioning
confidence: 99%
“…In addition, when posture is changed from standing to supine, plasma renin activity and plasma concentrations of aldosterone have been reported to decrease 16 and plasma arterial natriuretic peptide to increase. 25 In this study, however, we did not measure these parameters. Further studies are required to clarify the mechanisms of the disturbed natriuresis in non-dippers.…”
mentioning
confidence: 99%